2017
DOI: 10.1136/bmjopen-2016-013706
|View full text |Cite
|
Sign up to set email alerts
|

Reducing depressive symptoms after the Great East Japan Earthquake in older survivors through group exercise participation and regular walking: a prospective observational study

Abstract: ObjectivesSurvivors of the 2011 Great East Japan Earthquake have an increased risk of depressive symptoms. We sought to examine whether participation in group exercise and regular walking could mitigate the worsening of depressive symptoms among older survivors.DesignProspective observational study.SettingOur baseline survey was conducted in August 2010, ∼7 months prior to the Great East Japan Earthquake and tsunami, among people aged 65 or older residing in Iwanuma City, Japan, which suffered significant dama… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…The implication of this study is that fostering neighborhood ties after a natural disaster may be able to alleviate the deterioration of depression, even among the older survivors who did not have neighborhood ties before the disaster; in other words, social ties with neighbors might function as a resource for the survivors' psychological health even in disaster affected areas. Public health interventions can also increase older people's opportunities to participate in social activities and improve their social interactions after the disaster via physical activities such as walking exercise, which had a significant association with the changes in the depressive symptoms both in this study and a previous one [44].…”
Section: Discussionsupporting
confidence: 55%
“…The implication of this study is that fostering neighborhood ties after a natural disaster may be able to alleviate the deterioration of depression, even among the older survivors who did not have neighborhood ties before the disaster; in other words, social ties with neighbors might function as a resource for the survivors' psychological health even in disaster affected areas. Public health interventions can also increase older people's opportunities to participate in social activities and improve their social interactions after the disaster via physical activities such as walking exercise, which had a significant association with the changes in the depressive symptoms both in this study and a previous one [44].…”
Section: Discussionsupporting
confidence: 55%
“…For instance, meta-analysis across 148 articles mentioned active engagement in social activities could reduce risk for mortality. In particular, previous observational studies in Japan also found that collective social participation activities such as volunteering, sports clubs and hobbies among older adults lowered the risk of developing depressive symptoms,11–13 the incidence of functional disabilities,14–16 cognitive decline or dementia,17 18 falls19 and immature death 20–23…”
Section: Introductionmentioning
confidence: 95%
“…Physical activity, which is a modifiable behavior, can prevent or alleviate depressive symptoms in older individuals ( 3 6 ). In particular, group participation in sports may have positive effects of physical activity and social participation on mental health ( 7 11 ), leading to enjoyment, enhanced self-esteem, and decreased stress ( 8 ). Increasing the frequency of sports group participation may alleviate the worsening depressive symptoms among older individuals who walk at an even rate compared with those who increase their daily walking time ( 11 ).…”
mentioning
confidence: 99%